PERILAKU BELI WISATAWAN SUBOSUKOWONOSRATEN TERHADAP OBYEK WISATA TAMAN SATWA TARU JURUG SURAKARTA - Setyadi, M. Gunawan; Maryam (UNIBA Surakarta), Siti (Manajemen Bisnis Syariah, 2011)
Taman SatwaTaru Jurug is a tourism object of zoo whict is possessed by government municipal of Surakarta, but since it’s establishment of TSTJ, its band has not yet established positively, and ever there is tendency that its popularity experienced more decreased. With establishment of tourism object in other region, so the communities have many choices to visit tourism object, so the the existence of Taman Wisata Taru Jurug as tourism object is placed by new tourism objects.                  The goals of this research is to know the impact of dimension variables of service quality, motivation, consumer perception, the history force of Jurug, social culture, willingness to pay, motivation, promotion activity, and the attitude of the consumers against decision to consume of TSTJ. This research is performed by using causal-conclusive research design which has main goal to test a hypothesis or the relation which is described in model of hypothetic, in this research the relation is proved by Structure Equation Modeling (SEM). Data collecting method used is survey to TSTJ visitors. Based on the result of data analysis, it can be concluded that: 1) Dimension of service quality influenced promotion activity; 2) Consumers perception, promotion activities, motivation of the consumer influenced consumer attitude, while variables of Jurug history, social culture and willingness to pay did not influence consumer’s attitude; 3) tangible dimension influenced the decision to buy of the consumers; 4) perception of the consumers did not influence the decision to buy of the consumers; 5) the history of Jurug, social culture, promotion activities, willingness to pay, comsumer’s motivation influenced significantly decision to buy of the consumers; 6) The attitude of the consumer has function to strengthen the perception impact of consumer against decision to buy of the consumer; 7) Based on causality test and the suit of the model , so it can be concluded that there is the impact of service quality dimension , consumer perception, the force of Jurug history, social culture of Solo, willingness to pay, motivation, marketing activities, and consumer attitude against decision to buy of the consumers of Taman Satwa Taru Jurug (TSTJ). Keyword: Jurug zoo, consumerism behavior of the consumers, service quality dimension, perception,                         History of Jurug, social culture, promotion activities, willingness to pay, consumer’s attitude,                           motivation